Headache and migraine in practice - Togha, Mansoureh; Jafari, Elham; Ansari, Hossein; Haghighi, Samaneh; Mohammadianinejad, Seyed Ehsan (Academic Press, 2022)
Headache and Migraine in Practice provides practical and precise approaches to the headaches and facial pains commonly encountered in hospitals and clinics. The book pays specific attention to the clinical features of headaches to present treatment solutions, while also recommending ICHD3 differential diagnoses based on diagnostic criteria. Topics covered were developed by colleagues with expertise in Neurology, Nutrition, Psychiatry, Physical Medicine, and Sports Medicine, thus providing a collaborative authorship that adds interdisciplinary value. Sections cover the diagnosis and treatment of various types of headaches in children, the elderly and women during different periods of pregnancy, lactation and hormone-related stages.